Euro Area : Staff Report on the Monetary and Exchange Rate Policies of the Euro Area and the Trade Policies of the European Union; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director on Monetary and Exchange Rate Policies of the Euro Area. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines the monetary and exchange rate policies of the euro area and the trade policies of the European Union. The paper highlights that the overall economic performance of the euro area has been disappointing: growth has been weaker and inflation higher than generally expected. To a large extent, this is the result of a series of unanticipated shocks-oil prices and animal diseases earlier, and the global slowdown and the associated financial market turmoil more recently. However, the performance also appears to reflect a greater-than-anticipated vulnerability to shocks.